Current status of diagnostic and therapeutic colonoscopy in Japan: The Japan Endoscopic Database Project. Issue 1 (4th May 2021) - Saito, Yutaka; Kodashima, Shinya; Matsuda, Takahisa; Matsuda, Koji; Fujishiro, Mitsuhiro; Tanaka, Kiyohito; Kobayashi, Kiyonori; Katada, Chikatoshi; Horimatsu, Takahiro; Muto, Manabu; Ohtsuka, Kazuo; Oda, Ichiro; et al.
Abstract : Objectives: The Japan Endoscopy Database Project was initiated to develop the world's largest endoscopy data repository. This study describes the first phase of the colonoscopy project in Japan. Methods: Data were aggregated offline by integrating information from the endoscopy database software from January 2015 through March 2017. The study population included all patients who underwent colonoscopy at eight centers. Results: A total of 31, 395 patients who underwent 38, 497 colonoscopy procedures were registered. The majority of procedures were performed for screening ( n  = 14, 156), followed by fecal immunochemical test positivity ( n  = 3960), abdominal symptoms ( n  = 3864), post‐colorectal surgery surveillance ( n  = 3431), post‐endoscopic treatment surveillance ( n  = 3757), thorough pre‐treatment examination ( n  = 2822), and therapeutic purposes ( n  = 6507). In the screening group, advanced cancers, early cancers, and adenomas were diagnosed endoscopically in 2.1%, 1.3%, and 28.7% of cases, respectively, while in the fecal immunochemical test‐positive group, they were diagnosed in 2.5%, 1.9%, and 41.6% of cases, respectively. The incidence of complications was 0.177% and 0.152% in the screening and fecal immunochemical test‐positive groups, respectively. The therapeutic procedures included 1446 cold forceps polypectomy procedures, 4770 cold snare polypectomy procedures, 368 hot biopsies, 2998 hot snare polypectomy procedures, 9775 endoscopic or piecemeal endoscopic mucosal resections, and 1660 endoscopic submucosal dissections. A total of 173 procedure‐related complications (0.82%) occurred in 21, 017 therapeutic procedures performed in 15, 744 patients. Conclusions: The first phase of the Japan Endoscopy Database Project established the proportions of the diagnostic and therapeutic colonoscopy procedures, and complication rates in real‐world settings.